Comparative in vitro study on free radical scavenging potential of selected bivalve species - Shenai-Tirodkar, P.S.; Pawar, R.T.; Jagtap, T.G. (Progress in Nutrition, 2012)
Bivalves such as, Crassostrea spp., Meretrix casta, Placuna placenta and Polymesoda erosa are largely consumed as edible seafood. It forms natural source of nutrition in coastal and worldwide population. Free radical scavenging activities of these species were tested against 2, 2–diphenyl–1–picryl–hydrazyl (DPPH), hydroxyl radical (·OH), reducing power and in vitro inhibition of lipid peroxidation (LPX). Methanolic extracts exhibited dose dependency with increasing concentration (3 to 9 mg/ml) of sample. On comparing DPPH activities, M. casta and P. placenta statistically exhibited significant radical scavenging properties (p M. casta> P. erosa > Crassostrea spp. This indicates protective role against deterioration cell membrane lipids during oxidative stress. Moreover, correlation of variables (p P. erosa > Crassostrea spp. This indicates protective role against deterioration cell membrane lipids during oxidative stress. Moreover, correlation of variables (p